2017
DOI: 10.1038/s41598-017-13424-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium chloride effect on the aggregation behaviour of rhamnolipids and their antifungal activity

Abstract: In this work, the antifungal activity of rhamnolipids produced by Pseudomonas aeruginosa #112 was evaluated against Aspergillus niger MUM 92.13 and Aspergillus carbonarius MUM 05.18. It was demonstrated that the di-rhamnolipid congeners were responsible for the antifungal activity exhibited by the crude rhamnolipid mixture, whereas mono-rhamnolipids showed a weak inhibitory activity. Furthermore, in the presence of NaCl (from 375 mM to 875 mM), the antifungal activity of the crude rhamnolipid mixture and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
4
27
0
6
Order By: Relevance
“…Accordingly, we found that both the length of the fatty acid tail but also the nature of the bonds in the molecules influenced both the ROS response and increased resistance in plant in controlled conditions. RLs were previously described for their direct antifungal effect [25,30,32,[53][54][55]. In the present study, a similar effect of smRLs was demonstrated against B. cinerea through an inhibition of conidial germination as well as an alteration of mycelial growth.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Accordingly, we found that both the length of the fatty acid tail but also the nature of the bonds in the molecules influenced both the ROS response and increased resistance in plant in controlled conditions. RLs were previously described for their direct antifungal effect [25,30,32,[53][54][55]. In the present study, a similar effect of smRLs was demonstrated against B. cinerea through an inhibition of conidial germination as well as an alteration of mycelial growth.…”
Section: Discussionsupporting
confidence: 78%
“…RLs were previously described for their direct antifungal effect [ 25 , 30 , 32 , 53 , 54 , 55 ]. In the present study, a similar effect of smRLs was demonstrated against B. cinerea through an inhibition of conidial germination as well as an alteration of mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…To date, RL mode of action as antimicrobial compound is not elucidated. Their aggregation behavior could be related to their antifungal activities ( Rodrigues et al, 2017 ). On Alternaria alternata , microscopy observations revealed that RLs cause morphological structure alterations in the hyphae, probably due to increased cell permeability with DNA and protein leakages ( Yan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biosurfactants have been reported to exhibit antimicrobial activity via different mechanisms of action, which primarily destroy the cell wall or plasma membrane by disrupting their integrity and permeability [ 65 , 68 , 117 , 118 ]. More specifically, their amphiphilic characteristics and affinity for lipid bilayers allow BSs to interact with cell membranes, leading to cell lysis and metabolite leakage, which ultimately results in cell death [ 116 ].…”
Section: Marine Microbial-derived Biosurfactants: New Agents Against Cautismentioning
confidence: 99%